Kajian Linguistik Antropologi terhadap Istilah Kekerabatan dalam Bahasa Wewewa Sumba Barat Daya - Kami, Kanisius; Bili, Mace (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to describe kinship terms in the Wewewa language through an anthropological linguistic approach with a focus on analyzing the social structure, culture and interpersonal relationships of the Wewewa community. The data collected is in the form of words and phrases related to kinship terms in the Wewewa language. Analysis was carried out to explore the cultural meaning contained in language and understand the construction of cultural meaning in the expressions used by informants. The research results identified kinship terms structured based on age hierarchies, which influence social norms related to respect, courtesy and trust in daily interactions.